2016
DOI: 10.1136/bmjopen-2016-011124
|View full text |Cite|
|
Sign up to set email alerts
|

Conflict of interest between professional medical societies and industry: a cross-sectional study of Italian medical societies’ websites

Abstract: ObjectiveTo describe how Italian medical societies interact with pharmaceutical and medical device industries through an analysis of the information available on their websites.DesignCross sectional study.SettingItaly.Participants154 medical societies registered with the Italian Federation of Medical-Scientific Societies.Main outcome measuresIndicators of industry sponsorship (presence of industry sponsorship in the programme of the last medical societies’ annual conference; presence of manufacturers’ logos on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
3
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 15 publications
1
29
3
8
Order By: Relevance
“…Competing interest in biomedical research has often been associated with a positive conclusion with suppression of negative results [19,20,[37][38][39]. However, we did not nd the association between positive conclusion and competing interest disclosure in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…Competing interest in biomedical research has often been associated with a positive conclusion with suppression of negative results [19,20,[37][38][39]. However, we did not nd the association between positive conclusion and competing interest disclosure in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…Another important factor is the marketing policies used by the pharmaceutical industry, primarily to target GPs. Indeed, up to several years ago pharmaceutical companies were one of the main sources of information for GPs in both countries [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Of 154 Italian medical societies, 65 percent received private sponsorship for their last conference, 29 percent had manufacturers' logos on their webpage, and 36 percent had industry-sponsored satellite symposia at their last conference. 26 A large study showed that financial relationships between organizations that produce medical guidelines and individuals who sit on guidelines committees are common and that poor disclosure of conflict is linked to more positive statements about patented biomedical products. 27 Conflicts of interest surrounding guidelines do not produce concerns just about treatment but also about disease classification and diagnostic tools.…”
Section: Grants ($) Funds ($)mentioning
confidence: 99%